Internalization of Islamic Religious Education and Ethics Values in extracurricular Scouting Activities for the Formation of Islamic Leadership Spirit - Hadi, Muhammad Wafi Hilman Luthfil; Ali, Mohamad; Mustofa, Triono Ali (Hikmah, 2025)
This study discusses the internalization of Islamic Religious Education values and morals in Scouting extracurricular activities at school as an effort to integrate religious education with students' self-development activities. This integration is expected to shape individuals who are balanced between worldly and spiritual needs. This study aims to determine the planning, implementation, and supporting and inhibiting factors of the internalization of Islamic Religious Education values in Scouting activities. The method used is a qualitative approach with descriptive research, while data collection techniques include observation, interviews, and documentation. The results of the study show that the planning of value internalization is carried out systematically through short-term and long-term programs. The short-term program is in the form of weekly Scouting held every Saturday, while the long-term program includes annual activities such as Guest Reception, Scout Expedition, and Scout Action Movement. The implementation of value internalization takes place through the stages of value transformation, value transaction, and trans internalization. Supporting factors include school identity, the role of coaches, the availability of facilities, and student discipline, while inhibiting factors include the absence of coaches, boredom, and low creativity among some students.